Pernikahan Wisata Perspektif Hukum Islam - Sapri Ali (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Tourist marriage or misyar is illegitimate because it can damage the family and can cause problems in citizenship, because if a man visits four countries and in each country, he has a wife then there will be a mixture of offspring (ikhtilat nasab) which is prohibited by shari'a. Misyar (Tourism) marriage is carried out not based on achieving a purpose of marriage because the marriage is only done to eliminate the value of adultery in the purpose of marriage, but it is still haram because it has a mudharat that will occur in the future. And this marriage only fulfils the concept of maqasid al-shari'ah which is maqashid al-Asl iyyah (the main purpose) but not maqashid tabi'iyah.